Application of Particle Size Distribution Engineering and Nano-technology to Cement Recipes for some Iranian Offshore Oilfields - Yaser Pourmazaheri (Journal of Petroleum Science and Technology, 2015)
The design of cement slurry for horizontal wellbores is challenging as it must present very high quality cement slurry properties e.g. zero free water, less than 50 cc API fluid loss value, appropriate rheology and yield point for effective displacement, adequate compressive strength, which is critical for lightweight slurries, and finally stable cement column behind casing. The main objective of these requirements is to provide unique cement sheath in the upper side of annulus as well as the lower side and to guarantee complete zonal isolation. These requisite conditions could be rarely met especially when lightweight cement is needed. Four cement recipes were made and named as RIPI-1 through RIPI-4 representing standard slurry with a density of 118 pounds per cubic feet (pcf), traditional lightweight slurry with a density of 90 pcf, lightweight slurry with engineered PSD and nanoparticles in a liquid form, and finally another type of PSD and nanopowder respectively. These slurries were tested at the temperature and pressure of Iranian Balal, Soroush, and Siri oilfields and finally were compared with those slurries previously used in the oilfields. According to the results, reductions in yield point up to 84% and in fluid loss value up to 44% were recorded by the recipes. Moreover, an increase in compressive strength up to 82% was measured and the maximum strength of 2500 psi was obtained for slurry RIPI-4. All the slurries designed showed adequate stability. However, significant improvements were achieved by slurries RIPI-3 and RIPI-4 with engineered PSD and nanoparticles.